Determining ‘Uqūbāt for Sexual Harassment and Rape from the Perspective of Maqāṣid al-Sharīʿah: An Analysis of Mahkamah Syar’iyah Singkil Decision - Zulkarnaini, Zulkarnaini (MAQASIDI: Jurnal Syariah dan Hukum published by the Islamic Criminal Law Program of the Sharia and Islamic Economics Department at the Sekolah Tinggi Agama Islam Negeri Teungku Dirundeng Meulaboh, 2025)
This study aims to analyze the selection of ‘uqubat ta’zir (discretionary punishments) in verdicts concerning jarimah (criminal acts) of sexual harassment and rape at the Mahkamah Syar’iyah Singkil during the period of 2021–2023, as well as to examine the judges' considerations through the lens of maqashid shariah (objectives of Islamic law). The study focuses on the implementation of the Supreme Court Circular (SEMA) and its alignment with maqashid shariah values in the determination of ‘uqubat ta’zir. This study uses a library research method to draw on primary data from Mahkamah Syar’iyah Singkil verdicts and interviews, alongside secondary data from regulations, qanun (regional Islamic laws), and relevant literature. The research adopts a normative juridical approach. The findings indicate that the panel of judges has implemented SEMA No. 10 of 2020 by imposing ‘uqubat ta’zir in the form of imprisonment. This implementation reflects a preventive effort against recidivism, a form of protection and recovery for victims, as well as a means of legal education (tadabbur) for society. Normatively, the judges' considerations align with the principles of maqashid shariah, particularly in the aspect of hifz al-nafs (protection of life). However, the application of hifz al-nasl (protection of lineage) and hifz al-mal (protection of property) has not been optimal, as no verdicts during the study period included restitution orders for the victims. Therefore, integrating restitution components into verdicts is crucial to strengthening the elements of public welfare (maslahah) and substantive justice within the jinayat judicial system.